Prospective observational study to evaluate dermatology life quality index in patients with lichen sclerosus presenting to a tertiary care centre in Nepal - Shrestha, Elisha; Singh Basukala, Manisha; Mishra, Aditi; Shahi, Khushbu; Tamang, Ashish (Journal of Chitwan Medical College, 2025)
Introduction: Lichen sclerosus (LS) is a chronic inflammatory skin disease affecting the genital area, often leading to physical discomfort, anatomical changes, and reduced quality of life (QOL). The impact on QOL remains underexplored, particularly in resource-limited. Method: This prospective observational study on patients clinically diagnosed with LS who attended the dermatology outpatient department of Dhulikhel Hospital, Nepal, over six months from Jan to Jun 2024, after ethical approval. The QOL was assessed using validated Nepali version of Dermatology Life Quality Index (DLQI). Sociodemographic and clinical data were analysed for factors associated with higher impairment scores. A p-value <0.05 was considered statistically significant Result: The median DLQI score was 24 (IQR 18–26). Most participants experienced very large (38.46%) or extremely large (58.97%) effects on QOL. Highest impact was observed in clothing choices (Q4: 2 [IQR 2–3]), itching or pain (Q1: 2 [IQR 2–3]), and limitation in sports (Q6: 3 [IQR 2–3]). Postmenopausal women (median DLQI 23 [IQR 20–26]), homemakers (24 [IQR 20–26]), and those from rural areas like Ramechap (24 [IQR 18–30]) and Kavre (24 [IQR 20–26]) had higher impairment scores. Bivariate analysis showed a significant association between homemaker and high DLQI scores (p=0.006), while age trended toward higher DLQI but was not statistically significant (p=0.076). Comorbidity was not significantly associated with impairment (p=0.215). Conclusion: The LS imposes a substantial QOL burden, particularly among women from disadvantaged backgrounds. Incorporating routine QOL assessment into clinical care can improve patient-centred management and outcomes.